Thainess Tourism Needs: A Case Study of Adolescents Studying at Thammasat University - Chaijan, Khunyarin (Journal of Cultural Approach, 2020)
The objectives of this research aimed to study tourism behavior, perception, and need of Thainess tourism: a case study of adolescents studying at Thammasat University. Survey research was conducted by collecting data from 400 first-year students by using non-probability sampling and accidental selection. The research findings showed that half of the tourists traveled more than three times a year, mostly travel with families during the holiday weekend, use a private car as a vehicle and prefer to stay at hotels. Most tourists are not aware of Thainess tourism, which is outstanding to think in a way of life and traditions. Besides, in terms of feeling in traveling, most tourists have peace of mind. Moreover, the needs for tourist attractions and activities are at a high level. Most activities are the need for food, eating and Trat province as a dream island city.